Baroreflex sensitivity following acute upper-body exercise in the cold among stable coronary artery disease patients - Pikkarainen, Kalle; Valtonen, Rasmus I. P.; Hintsala, Heidi E.; Kiviniemi, Antti; Crandall, Craig G.; Perkiömäki, Juha; Hautala, Arto J.; Tulppo, Mikko P.; Jaakkola, Jouni J. K.; Ikäheimo, Tiina M. (Frontiers in Physiology, 2023)
Background: A cold environment and exercise separately affect the autonomic nervous system (ANS), baroreflex sensitivity (BRS), and blood pressure variability (BPV) but their combined effects on post-exercise recovery are not known. Our cross-over trial examined these responses following upper-body static and dynamic exercise performed in a cold and neutral environment in patients with coronary artery disease (CAD). Methods: 20 patients with stable coronary artery disease performed both graded static (10%–30% of maximal voluntary contraction) and dynamic (light, moderate and high perceived intensity) upper-body exercise at −15°C and +22°C for 30 min. Electrocardiogram and continuous blood pressure were measured to compute post-exercise (10 and 30 min after exercise) spectral powers of heart rate (HR), blood pressure variability and BRS at low (0.04–0.15 Hz) and high (0.15–0.4 Hz) frequencies. Results: Static upper-body exercise performed in a cold environment increased post-exercise high frequency (HF) spectral power of heart rate (HF RR) (p < 0.001) and reduced heart rate (p = 0.001) and low-to-high frequency (LF/HF) ratio (p = 0.006) more than in a neutral environment. In addition, post-exercise mean BRS (p = 0.015) and high frequency BRS (p = 0.041) increased more following static exercise in the cold than in a neutral environment. Dynamic upper-body exercise performed in a cold environment reduced post-exercise HF BRS (p = 0.019) and systolic blood pressure (p = 0.003). Conclusion: Static upper-body exercise in the cold increased post-exercise BRS and overall vagal activity but without reduced systolic blood pressure. Dynamic upper-body exercise in the cold reduced post-exercise vagal BRS but did not affect the other parameters. The influence of cold exposure on post-exercise autonomic and cardiovascular responses following static upper-body exercise require further studies. This information helps understanding why persons with cardiovascular diseases are vulnerable to low environmental temperature. ClinicalTrials.gov: NCT02855905 (04/08/2016).